In Silico Toxicological Analysis of Active Compounds Present in Selected Pesticides Sold in South-West Nigeria - Daniel Uwaremhevho Momodu; Toluwase Hezekiah Fatoki; Alebiosu, Oluwaseyi Samuel; Ojo, Deborah Ebunoluwa; Akinlolu, Olapade Samuel; Oyebanji, Adedayo Olamide (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: The study investigated the molecular effects of human exposure to commonly used pesticides in Nigeria. Methods: Utilizing computational methods like clustering analysis, toxicokinetic predictions, molecular docking, and molecular dynamic (MD) simulation, various health impacts were identified. Results and Discussion: The results revealed significant gastrointestinal absorption, P-glycoprotein bypass, blood-brain barrier penetration, and cytochrome P450 inhibition for certain pesticide agents. Notably, oxathiapiprolin showed hepatotoxicity, propanil exhibited drug-induced liver injury (DILI), and 2,4-dichloro-phenoxyacetic acid demonstrated carcinogenicity. Respiratory toxicity was predicted for most pesticides, except propanil and N-(2,6-diethylphenyl) acetamide. Molecular targets were identified, such as bifenthrin targeting programmed cell death 1 ligand 1 and Atrazine targeting potassium voltage-gated channel subfamily H member 3. Binding affinities were computed, with oxathiapiprolin showing -6.526 kcal/mol with short transient receptor potential channel 7. Molecular dynamic simulations indicated significant binding energy changes over time. Atrazine's binding with potassium voltage-gated channel subfamily H member 3 exhibited a total binding energy ΔGbind of -39.410 kcal/mol and -49.135 kcal/mol at 0 ns and 100 ns, respectively. Oxathiapiprolin's binding with short transient receptor potential channel 7 showed ΔGbind of -53.481 kcal/mol and -44.122 kcal/mol at 0 ns and 100 ns. Conclusion: This study suggests potential hepatotoxicity and carcinogenicity of certain pesticides, emphasizing the need for environmental monitoring and stringent regulations to safeguard public health.